Monetary Union, Entry Conditions and Economic Reform. - F. Gulcin Ozkan; Anne Sibert; Alan Sutherland (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
This paper models the behaviour of a potential entrant into a monetary union where there is an inflation entry condition. In addition to making a monetary policy decision during a qualifying period, the potential entrant must make a decision about structural reform. The paper shows that the entry condition can have two undesirable effects. First, it can lead to multiple equilibria because inflationary expectations acquire a self-fulfilling property. Second, the entry condition can lead to a reduction in the amount of reform. This is because the entry condition reduces inflationary expectations and thus reduces the incentive to reform.
Keywords: 330